2017
DOI: 10.1039/c6ob02241c
|View full text |Cite
|
Sign up to set email alerts
|

Second-generation total synthesis of aplyronine A featuring Ni/Cr-mediated coupling reactions

Abstract: Second-generation total synthesis of aplyronine A, a potent antitumor marine macrolide, was achieved using Ni/Cr-mediated coupling reactions as key steps. The overall yield of the second-generation synthetic pathway of aplyronine A was 1.4%, obtained in 38 steps based on the longest linear sequence. Compared to our first-generation synthetic pathway of aplyronine A, the second-generation synthesis greatly improved both the yield and number of steps. In particular, we improved the stereoselectivity in the const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…For bioassay, a part of the sample was further purified with reversed-phase HPLC [Develosil ODS-HG-5 (ϕ 20 × 250 mm), MeOH/20 mM aq NH 4 OAc (74/26), 5 mL/min, UV254 nm, t R 31.3–35.3 min]. As with previous synthetic studies of aplyronines, epimerization of the TMSer ester moiety was observed during condensation. While compound 5 was separable as a mixture of two stereoisomers by reversed-phase HPLC, bioassays were carried out with a mixture of four stereoisomers.…”
Section: Experimental Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For bioassay, a part of the sample was further purified with reversed-phase HPLC [Develosil ODS-HG-5 (ϕ 20 × 250 mm), MeOH/20 mM aq NH 4 OAc (74/26), 5 mL/min, UV254 nm, t R 31.3–35.3 min]. As with previous synthetic studies of aplyronines, epimerization of the TMSer ester moiety was observed during condensation. While compound 5 was separable as a mixture of two stereoisomers by reversed-phase HPLC, bioassays were carried out with a mixture of four stereoisomers.…”
Section: Experimental Sectionsmentioning
confidence: 99%
“…The use of PPI-stabilizing or -inhibiting scaffolds has important implications for simplified mimetic design and provides new insights into ways to design molecules that tether proteins using different binding surfaces . Among a small number of natural products that simultaneously interact with more than one biomacromolecule, aplyronine A (ApA, 1 ), a 24-membered antitumor macrolide isolated from the sea hare Aplysia kurodai, promotes a unique PPI between actin and tubulin, two of the major cytoskeletal proteins (Figure ). ApA was originally characterized as an actin-targeting agent that depolymerizes fibrous actin (F-actin) and inhibits the polymerization of actin by forming a 1:1 complex with the monomeric globular molecule (G-actin) .…”
Section: Introductionmentioning
confidence: 99%